Preclinical Evaluation of Esomeprazole Safety and Toxicokinetics - V. M. Kosman; M. V. Karlina; E. V. Mazukina; A. A. Globenko; E. A. Jain; M. N. Makarova; V. G. Makarov (Безопасность и риск фармакотерапии, 2023)
Esomeprazole, the S-isomer of omeprazole, is a second-generation proton pump inhibitor widely used for acid-related diseases of the oesophagus, stomach, and duodenum (peptic ulcer, gastro-oesophageal reflux disease, etc.). Studies on esomeprazole safety and toxicokinetics (TK) are essential for increasing the number of modified-release esomeprazole products manufactured in Russia.The aim of the study was to compare the safety and toxicokinetics of a new esomeprazole product, 40 mg modifiedrelease capsules (Valenta Pharm JSC, Russia), and Nexium® 40 mg film-coated tablets (AstraZeneca AB, Sweden).Materials and methods. This toxicity study involved oral administration of esomeprazole 40 mg modified-release capsules (Valenta Pharm JSC, Russia) and Nexium® 40 mg film-coated tablets (AstraZeneca AB, Sweden) to 5 groups of rabbits (8 males and 8 females per group) for 28 days at a dose of 1 or 3 capsules, or tablets, corresponding to approximately 4.8 or 14.3 maximum human therapeutic doses (MHTDs), respectively. Comparisons included general toxicity, local tolerance, safety pharmacology, effects on immune system organs, reproductive toxicity, and basic TK parameters (Cmax, Tmax, AUC0-24, MRT, and T1/2).Results. No toxic effects, including local irritation and immunotoxicity, were observed for the test product. The safety pharmacology testing demonstrated the safety of repeated oral administration of the test product for the cardiovascular, excretory, respiratory systems and the liver. The test product did not affect the reproductive system of male and female rabbits. The No Observed Adverse Effect Level (NOAEL) was determined to be 14.3 MHTDs. According to the TK parameters evaluated after single and repeated oral administration, the test product and Nexium® demonstrated comparable TK profiles.Conclusions. The study demonstrated a favourable safety profile for the test product. All the test product parameters studied were comparable with those of Nexium®. Positive clinical experience with Nexium® supports the data obtained for the new esomeprazole product. Thea safety of these medicinal products may be considered similar.